THE SYSTEMATIC REVIEW OF OSTEOPOROSIS AND BONE FRACTURES IN ALCOHOLIC LIVER DISEASE - Giovani, Calista; Monica Carissa, Theodora; Priska Adelin, Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Osteoporosis is classified as primary when it is age-related or occurs in postmenopausal women and secondary when caused due to other etiologies. Previous studies have shown that the prevalence of osteoporosis in patients with cirrhosis ranges from 12 to 70 based on the diagnostic approach and etiology of the underlying liver disease. The aim: This study aims to show osteoporosis and bone fractures in alcoholic liver disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 29 articles, whereas the results of our search on SagePub brought up 77 articles. The results of the search conducted for the last year of 2013 yielded a total 21 articles for PubMed and 28 articles for SagePub. The result from title screening, a total 10 articles for PubMed and 17 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The liver is an organ involved in a number of metabolic and hormonal processes whose dysregulation may lead to the development of bone homeostasis disorders and ultimately to osteopenia and osteoporosis. Complications of chronic liver disease should therefore include pathologic osteoporotic fractures, which significantly reduce quality of life.